The cat who came for Christmas - Amory, Cleveland; Edith Allard (New York : Penguin Books, 1988)
'Twas the night before Christmas when a bedraggled stray white feline entered the home, and heart, of Cleveland Amory. At first the relationship seemed a clash of two stubborn wills, but despite the battles, Polar Bear did finally recognize his new name, while he settled into a comfortable friendship. A delightful true tale for anyone who has ever been owned by a cat or any pet.
Keywords: AMORY, CLEVELAND